(untitled) (International Journal of Technology and Management Research, 2021)
Fast food vendors use a sensory cue to trigger impulsive buying behaviour. Though impulse buying has gained interest among researchers, little has been done concerning food in Ghana. The purpose of the study was to investigate the contribution of the sensory cue on customer’s emotions and cognition and impulsive buying behaviour. The study finds answers to the succeeding research questions: what sensory cue impacts on consumer emotion and cognition? And does emotion and cognition influence consumer’s impulsive buying behaviour. A proposed theoretical model identifies visual, audio, and tactile dimensions as the sensory cue, emotions, and cognitive as mediation variable and impulsive buying behaviour as the outcome. Data were collected from 241 customers who were residence in Tema and have patronized the services of food vendors for a minimum of two years using a convenience sampling technique. The suggested hypothesis was tested using structural equation modeling and hierarchical multiple regression analysis. The result of the study shows that visual, audio, and tactile dimensions have a positive relationship with emotion but a negative relationship with cognition. Regarding directs effect, the study revealed that there is a positive relationship between emotion and impulsive buying behaviour whiles cognition has a negative effect on impulsive buying behaviour. The study recommended that managers must induce impulsive buying using characteristics of the food they serve and the environments in which they operate to stimulate customers’ arousal and pleasure and provide enough information to alleviate the risk customers consider before buying food. The findings may not be generalized since the data was collected in specific areas in Tema. Citation: Edward Markwei Martey, Racheal Markwei Martey and Kingsford Adenutsi. The influence of sensory cue on emotion, cognition and impulse buying behaviour of fast-food vendors in Ghana, 2020; 5(4): 12－29. Received: October 23, 2020 Accepted: December 31, 2020